Quintilian on the teaching of speaking & writing : translations from books one, two & ten of the Institutio Oratoria - Quintilian (Landmarks in rhetoric and public address., 2016)
"Quintilian on the Teaching of Speaking and Writing, edited by James J. Murphy and Cleve Wiese, offers scholars and students insights into the pedagogies of Marcus Fabius Quintilianus (ca. 35-ca. 95 CE), one of Rome's most famous teachers of rhetoric. Providing translations of three key sections from Quintilian's important and influential Institutio oratoria (Education of the Orator), this volume outlines the systematic educational processes that Quintilian inherited from the Greeks, foregrounding his rationale for rhetorical education based on the interrelationship between reading, speaking, listening, and writing, and emphasizing the blending of moral purpose and artistic skill. Translated here, Books One, Two, and Ten of the Institutio oratoria offer the essence of Quintilian's holistic rhetorical educational plan that ranges from early interplay between seen- and heard-language to later honing of facilitas, the readiness to use language in any situation. Along with these translations, this new edition of Quintilian on the Teaching of Speaking and Writing also contains an expanded scholarly introduction with an enhanced theoretical and historical section, an expanded discussion of teaching methods, and a new analytic guide directing the reader to a closer examination of the translations themselves. A contemporary approach to one of the most influential educational works in the history of Western culture, Quintilian on the Teaching of Speaking and Writing provides access not only to translations of key sections of Quintilian's educational program but also a robust contemporary framework for the training of humane and effective citizens through the teaching of speaking and writing. "--